Internações hospitalares de idosos do município de Passo Fundo (RS) por causas sensíveis à atenção primária - Higuchi, Daniela de Linhares Garbin (2020)
Hospitalizations for sensitive causes in the elderly may vary as a result of different health actions and policies (access, supply, assistance and resolution). The objectives were to verify hospitalizations for sensitive causes elderly to primary care in the city of Passo Fundo-RS, in the years 2008 and 2018; describe the sociodemographic characteristics of the sample, identify the prevalent diseases in HACSC for the elderly and their possible association with Health Family Strategy coverage in the municipality. This is a cross-sectional observational study with data from the National Health Information System, with a sample composed of 9,064 Hospital Admissions Authorizations (HAA) of the older adults in Passo Fundo hospitals, in the years 2008 and 2018. Data collection was performed on the hospital information website of the Unified Health System (SIH / SUS), available at the SUS IT department (DATASUS) of the Municipal Secretariat of Passo Fundo-RS. The variables evaluated were contemplated in the Hospital Admissions Authorizations (HHA) of the elderly and include sociodemographic data (age, sex, race, address) and related to the hospitalization procedure. The International Classification of Diseases Code for the authorized procedure (ICD-10) was used as the cause of the patient's hospitalization, and the outcome was defined and classified based on the Sensitive Care List, according to the Ordinance of the Ministry of Health nº 221, of April 17, 2008. The FHS coverage closest to the residential address registered with the HAA was sought. Descriptive analyzes were performed and for the associations the chi-square and Fisher's exact tests were applied. How results, were identified from the total of 9,064, 3,183 hospitalizations for the elderly in 2008 and 5881 hospitalizations in 2018. The prevalence of HACSC in the elderly in 2008 was 33.6%, with a reduction to 27.9% in 2018 (p <0.001). Of the total number of hospitalizations in the two years of observation, it was identified that there was a higher HACSC of elderly people aged 90 years or older, when compared to the other age groups (p <0.001). In the analysis of HACSC by year of hospitalization, it was identified that in 2008 the prevalence of HACSC was higher among the elderly aged 70 years or older and among those who lived in places with FHS coverage. In 2018, there was a higher prevalence among the elderly aged 90 years or older (p <0.001). During these two years, diseases of the circulatory and respiratory system were the most prevalent. The study concluded that the reduction of the HACSC from 2018 to 2008 was significant, however the relation with the area covered by the Family Health Strategy needs to be further investigated. The association with older adults and the most prevalent group of diseases, circulatory and respiratory system, is in accordance with the literature and it points to the need for public policies on prevention and early diagnosis.